ISLAMIC RELIGIOUS EDUCATION TEACHERS' STRATEGIES IN DEVELOPING SELF-REGULATION IN STUDENTS AT TAKHASSUS AL-QUR'AN SENIOR HIGH SCHOOL, WONOSOBO - Dena Nafikhatul Aulia; Maryono Maryono; Fatiatun Fatiatun (Alphateach (Jurnal Profesi Kependidikan dan Keguruan), 2026)
This study aims to examine the strategies of Islamic Religious Education teachers in fostering self-regulation in students at Takhassus Al-Qur'an Senior High School in Wonosobo, identify the forms of student self-regulation, and analyze the supporting and inhibiting factors. The study used a qualitative field approach with the subjects being the principal, vice principal for curriculum, PAI teachers, and students. Data were collected through observation, interviews, and documentation, then analyzed through the stages of reduction, presentation, and drawing conclusions. The results showed that PAI teachers' strategies were implemented through habituation of religious activities, role models, motivation, advice, supervision, and discipline development. Student self-regulation was reflected in the ability to plan and evaluate learning, internal motivation, and disciplined and responsible behavior, although some students still needed further guidance. Supporting factors included the religious school environment and school culture, while inhibiting factors included limited time, differences in student character, and the density of Islamic boarding school activities